Combined Steel Treatment with Calcium-Silicon; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Gizatulin R. A. Rinat Akramovich; Efremenkov А. В. Andrey Borisovich; Valuev D. V. Denis Viktorovich; Fedoseev S. N. Sergey Nikolaevich; Valueva A. V. Anna Vladimirovna (Materials Science in Mechanical Engineering, 2015)
Title screen